Fruit quality preservation of 'Fuyu' persimmon by preharvest and postharvest treatments with 1‑methylcyclopropene - Vieira, Marcelo José; Argenta, Luiz Carlos; Amarante, Cassandro Vidal Talamini do; Steffens, Cristiano André; de Souza, Edson Luiz (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to compare the effects of preharvest spraying of aqueous 1‑methylcyclopropene (1‑MCPa) and of postharvest treatment of gaseous 1‑methylcyclopropene (1‑MCPg) on fruit maturity and quality of 'Fuyu' persimmon (Diospyros kaki). Spraying of 150 mg L-1 1‑MCPa was done on trees in the first week of commercial harvesting. Fruit were harvested at 1, 7, 14, and 21 days after 1‑MCPa spraying (DAMS), and treated or not with 0.6 µL L-1 1‑MCPg one day after harvest. The treatments consisted of a control, 1‑MCPa, 1‑MCPg, and 1‑MCPa+1‑MCPg. Fruit were stored at 0°C for 70 days in modified atmosphere, followed by seven days at 23°C. The treatment with 1‑MCPa did not affect fruit maturity on trees, but reduced the premature flesh softening and the occurrence of translucent stain disorder at postharvest. The incidences of soft fruit after storage (average of three years) were higher than 84% for the control, and lower than 18% for fruit treated with 1‑MCPg, regardless of fruit harvesting date, and they were 15, 34, 40, and 75% for fruit treated with 1‑MCPa and harvested at 1, 7, 14, and 21 DAMS, respectively. The efficacy of 1‑MCPa is equivalent to that of 1‑MCPg for fruit harvested at 1 DAMS and its is reduced by delaying fruit harvest from the date of its application.